Cadaveric Arterial Vasculature of the Human Pancreas: A Recent Study - Kottapalli, Suresh Babu; Kumar, Sarangdhar; Gupta, Rakesh; Bobbara, Anakalayya (Current Innovations in Medicine and Medical Science Vol. 6, 2022)
The head of the pancreas is vascularized by the anterior and posterior pancreaticoduodenal arterial vessels. The body and tail are vascularized via the splenic artery. In 95.6% of instances, the posterior inferior pancreaticoduodenal artery (IPDA) is present. Adult human cadaver specimens are dissected at the Rohilkhand Medical College and Hospital in Bareilly to research the circulatory supply to the pancreas. The 30 specimens include more than a dozen both male and female specimens. The cadavers ranged in age from 35 to 50 years. The dorsal pancreatic artery (DPA) supplies the posterior surface of the pancreas. Many trivial branches usually arise from the splenic artery as it passes along the cranial margin and supplies the pancreas' body and tail. This work has demonstrated that splenic arteries developed these branches as they moved along the pancreatic upper margin. It is believed that a splenic artery or the celiac trunk, which starts in the spleen, supplies the dorsal pancreas' back surface. This study showed that the splenic carriageway does not supply the dorsal DPA. The IPDA.